2023
DOI: 10.3390/recycling8050069
|View full text |Cite
|
Sign up to set email alerts
|

Circularity Outlines in the Construction and Demolition Waste Management: A Literature Review

Izabella-Eva Gherman,
Elena-Simina Lakatos,
Sorin Dan Clinci
et al.

Abstract: This study provides a comprehensive view of the research field of construction and demolition waste (CDW) management in the circular economy based on a literature review. The increased intensity of interest is due to the need to create frameworks, mechanisms, and tools for the process of mind-shifting towards circularity. Research topics, researched life cycle stages, strategies for CDW management, sustainability assessment, building stock quantification, assessment tools and forecast methods, materials with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…Many of the research is based on Material Flow Analysis (MFA), which considers the inputs, stocks, and outputs of the system to estimate the expected amount of waste and can use top-down or bottom-up approaches. However, these are still very specific studies and difficult to replicate, as they depend on the availability of data in the region evaluated [60]. Given these difficulties, some studies combine the use of tools such as the Geographic Information System (GIS), BIM, and statistical analyses, among others.…”
Section: Methodologies Adopted In the Literature To Implement Buildin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the research is based on Material Flow Analysis (MFA), which considers the inputs, stocks, and outputs of the system to estimate the expected amount of waste and can use top-down or bottom-up approaches. However, these are still very specific studies and difficult to replicate, as they depend on the availability of data in the region evaluated [60]. Given these difficulties, some studies combine the use of tools such as the Geographic Information System (GIS), BIM, and statistical analyses, among others.…”
Section: Methodologies Adopted In the Literature To Implement Buildin...mentioning
confidence: 99%
“…Even so, several authors point to the unavailability of accurate data on construction materials and components as one of the major challenges for research [60,81]. Other obstacles are the lack of standardized methodologies for quantifying and evaluating the environmental impact of CDW, the costs and environmental impacts of transporting materials, which have a high density [82], and the short reuse gap due to construction deadlines from commercial partners and storage difficulties.…”
Section: Potential Applications Of Buildings As Materials Banks In Mi...mentioning
confidence: 99%
“…Many of these researches are based on a Material Flow Analysis (MFA), which considers the inputs, stocks and outputs of the system to estimate the expected amount of waste, and can use topdown or bottom-up approaches. However, these are still very specific studies and difficult to replicate, as they depend on the availability of data in the region evaluated [48]. Given these difficulties, some studies combine the use of tools such as the Geographic Information System (GIS), BIM, statistical analyses, among others.…”
Section: Methodologies Adopted In the Literature To Implement Buildin...mentioning
confidence: 99%
“…While Gamage, I. et al, 2024 [61] identified the relationships of highly cited circular practices in the literature, Karaca, F et al, 2024 [62] explained the concept of resource equity in the construction sector. Gherman, I.-E et al, 2023 [63] introduced a novelty in structuring the research trends. By studying the implementation of circular principles, researchers contribute to innovation theory, particularly in how new technologies and processes are adopted within the construction sector.…”
Section: Theoretical Contributionmentioning
confidence: 99%